2012
DOI: 10.1038/hr.2012.169
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced external counterpulsation creates acute blood flow patterns responsible for improved flow-mediated dilation in humans

Abstract: Enhanced external counterpulsation (EECP) is a FDA-approved treatment for patients with coronary artery disease and unstable angina. Although beneficial effects of EECP have been linked to central/cardiac adaptations, recent findings have shown peripheral/vascular effects. Here, we sought to determine EECP-induced blood flow patterns and their association with vascular function. The present study was designed to investigate endothelium-mediated arterial vasodilation changes after one 45-min session of either E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 40 publications
5
56
1
Order By: Relevance
“…During EECP, these cuffs are sequentially inflated, from distal to proximal, with target inflation pressures of 300 mmHg during cardiac diastole until rapid deflation immediately prior to systole. A single 45 min EECP session has been shown to acutely increase flow-mediated dilation (FMD) (Gurovich and Braith 2013), a surrogate of conduit artery endothelial function and nitric oxide bioavailability (Akhtar et al 2006). Chronically, administration of EECP has been shown to elicit significant improvements in FMD of the brachial (Hashemi et al 2008;Braith et al 2010;Beck et al 2014), femoral (Braith et al 2010;Beck et al 2014), and popliteal arteries .…”
Section: Introductionmentioning
confidence: 99%
“…During EECP, these cuffs are sequentially inflated, from distal to proximal, with target inflation pressures of 300 mmHg during cardiac diastole until rapid deflation immediately prior to systole. A single 45 min EECP session has been shown to acutely increase flow-mediated dilation (FMD) (Gurovich and Braith 2013), a surrogate of conduit artery endothelial function and nitric oxide bioavailability (Akhtar et al 2006). Chronically, administration of EECP has been shown to elicit significant improvements in FMD of the brachial (Hashemi et al 2008;Braith et al 2010;Beck et al 2014), femoral (Braith et al 2010;Beck et al 2014), and popliteal arteries .…”
Section: Introductionmentioning
confidence: 99%
“…37 At peak dilation brachial blood flow starts showing a bi-phasic flow pattern, with some retrograde laminar flow, as observed during resting measurements. Based on Womersley's approximation for pulsatile flows and an estimated hematocrit of 50%, 35,36 in the present study the blood-flow pattern at peak shear rate was confirmed as primarily antegrade and turbulent (data not shown). Normalizing FMD using AUC30 before peak dilation would include only antegrade laminar blood flow, which is known to guarantee endothelial activation.…”
Section: Discussionmentioning
confidence: 74%
“…14,15,23,24,32,33 AUC30 normalization is based on two physiological principles: (1) NO half-life 34 and (2) turbulent blood flow that might be present immediately after the cuff release, at the beginning of reactive hyperemia. 35 Peak FMD is normally observed 45-80 seconds after cuff deflation; 14 however, NO half-life is <10 seconds. 34 According to previous studies, 35,36 it is highly probable that blood flow during the first 15-30 seconds after cuff deflation is turbulent, which may inhibit endothelial function.…”
Section: Brachial Artery Flow-mediated Dilation (Fmd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cuffs were inflated at a high pressure (up to 300 mmHg), which greatly altered arterial physiological hemodynamics [19], blood flow was retrograde and turbulent in the femoral artery but anterograde and laminar in the brachial artery [20]. Nevertheless, Gurovich et al [21] have shown, in a study that included 18 young men (25±4 years), that a single 45-min session of EECP with a pressure of 250 mmHg increased FMD in the femoral and brachial arteries compared with baseline, despite different blood flow patterns (retrograde-turbulent blood flow in the femoral artery and anterograde-laminar blood flow in the brachial artery). Both flow patterns created acute increases in endothelial shear stress.…”
Section: Discussionmentioning
confidence: 99%